Comparative Evaluation of Microsurgical and Open Flap Debridement: A Clinical Study - Chowdhury, Sananda; Gupta, Shalini; Nagpal, Tarun; Minakshi, Minakshi; Amrita, Amrita; Chaudhary, Bharti (Journal of Neonatal Surgery, 2025)
Background/Aims: Open flap debridement (OFD) is a well-established surgical procedure in periodontal therapy. The incorporation of microsurgical techniques has been proposed to enhance clinical outcomes and patient comfort. This study aimed to compare the clinical efficacy of conventional open flap debridement with microsurgical-assisted open flap debridement. Materials and Methods: A total of 30 systemically healthy subjects diagnosed with chronic periodontitis were enrolled and randomly assigned into two groups: Group A (control) underwent conventional OFD, while Group B (test) received OFD with microsurgical techniques. Clinical parameters including probing pocket depth (PPD), clinical attachment level (CAL), gingival recession (GR), gingival bleeding index (GBI), wound healing index (WHI), and visual analog scale (VAS) for pain assessment were recorded at baseline and at 3 months postoperatively. Results: Both groups showed clinical improvement from baseline to 3 months. Statistically significant differences were observed in PPD and CAL between the two groups, with the test group showing superior outcomes (p = 0.048). The WHI improved significantly in both groups; however, the test group demonstrated better initial healing with a mean WHI of 2.00 ± 0.00 at baseline and 1.00 ± 0.00 at 3 months, compared to the control group which showed 2.93 ± 0.258 at baseline and 1.00 ± 0.00 at 3 months (p = 0.00). Subjective pain perception measured through VAS was lower in the test group, indicating enhanced patient comfort. Conclusion: Microsurgical-assisted OFD demonstrated improved clinical outcomes and better patient-reported healing compared to conventional OFD. These findings support the clinical advantages of incorporating microsurgical techniques in periodontal therapy.